Efektivitas Kompres Hangat Menggunakan Media Botol Plastik Air Mineral Terhadap Intensitas Nyeri Haid Hari Pertama Pada Remaja Putri Usia 15-19 Tahun Di Desa Swarangan - Isnawati Isnawati; Yuniarti -; Nur Rohmah Prihatanti; Rubiati Hipni (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2026)
Abstract Menstrual pain is a common complaint among adolescent girls and can interfere with daily activities. The prevalence of first-day menstrual pain among girls aged 15–19 in Swarangan Village is approximately 65%. Non-pharmacological therapies, such as warm compresses, have been reported to reduce pain; however, their use is still limited, and studies on adolescents are scarce. To determine the effectiveness of a warm compress using a mineral water plastic bottle on the intensity of first- day menstrual pain among adolescent girls 15-19 years old in Swarangan Village. This study employed a pre-experimental design with a one-group pre-test and post-test approach. The sample consisted of 30 adolescent girls experiencing first-day menstrual pain, selected using purposive sampling. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after administering a warm compress at 40°C for 15 minutes using a mineral water plastic bottle wrapped in a 19 × 17 cm towel. The Shapiro–Wilk normality test indicated that the data were not normally distributed; therefore, data analysis was conducted using the Wilcoxon Signed Rank Test with a significance level of p < 0.05.Data were analysed using the Wilcoxon Signed Rank Test with a significance level of p < 0.05. The mean pain intensity before the intervention was 4.17 with a standard deviation of 1.533, categorized as moderate pain, and decreased to 2.83 with a standard deviation of 1.642, categorized as mild pain, after the intervention. A total of 25 respondents experienced a reduction in pain, while 5 respondents showed no decrease. The analysis indicated a statistically significant difference (Z = −3.583; p = 0.000 < 0.05). Warm compress application using a mineral water plastic bottle is effective in reducing first-day menstrual pain intensity and may be recommended as a simple, low-cost and easily applied intervention for adolescent girls. Keywords: Menstrual pain intensity, Warm compress, Plastic bottle, Adolescent girls